Null effect of ginsenoside Rb1 on improving glycemic status in men during a resistance training recovery - Chang, W.; Tsai, Y.; Huang, C.; Hsieh, C.; Chaunchaiyakul, R.; Fang, Y.; Lee, S.Jahr (Journal of the International Society of Sports Nutrition, 2015)
Background: Ginsenoside Rb1, a principle active ingredients of Panax ginseng, has been shown to lower blood glucose in animals and increase insulin secretion in cultured insulinoma cells. The aim of this study was to determine the effects of daily ginsenoside Rb1 supplementation on circulating glucose and insulin levels in men during a 5-day recovery period after an acute bout of resistance exercise.